2021
DOI: 10.3389/fpsyg.2021.717528
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Cooperative Learning in Physical Education on the Learning of Action Skills and Learning Motivation

Abstract: This paper proposes a cooperative learning method for use in physical education, involving two different grouping methods: S-type heterogeneous grouping and “free” grouping. Cooperative learning was found to enhance the effectiveness of basketball skills learning and learning motivation. A comparison was made of the differences between action skills grouping (the control group) and “free” grouping (the experimental group). The ARCS Motivation Scale and Basketball Action Skills Test were used to measure results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
14
0
4
Order By: Relevance
“…Yang et al (2014) revealed that cross-cultural online collaborative learning through web 2.0 technology improves cross-cultural competency. Furthermore, research has shown that cooperative learning also improves motivation and achievement in areas other than EFL, such as research methods among tertiary level students (Tran, 2019), and physical education (C. Yang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al (2014) revealed that cross-cultural online collaborative learning through web 2.0 technology improves cross-cultural competency. Furthermore, research has shown that cooperative learning also improves motivation and achievement in areas other than EFL, such as research methods among tertiary level students (Tran, 2019), and physical education (C. Yang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Group processing relate to opportunities for students to reflect on their activities as a group to establish whether there are any challenges of concern or successes (Jakavonyte-Staskuviene et al, 2021). The effective implementation of CL requires that students in groups continuously assess each other and the group's performance to identify areas of weakness needing improvement as well as of strength needing to be leveraged on for future success (Yang et al, 2021). In their study, Jakavonyte-Staskuviene et al (2021) found that a reflection by students on how well group members work together and how to maintain anything good in the working relationships contributes significantly to the effective implementation of CL.…”
Section: 23mentioning
confidence: 99%
“…CL has been defined variously by different authorities with some calling it a strategy while others call it an approach. One of the mostly used definition of CL is that it is a teaching and learning approach or strategy in which students work together in small groups of two to six to assist each other to learn and succeed (Abraham, 2021;Yang et al, 2021). Khansa and Khaled (2017, p. 2) also define CL as "an instructional strategy that involves small groups of students and that employs a variety of techniques to promote active learning by ensuring that students are responsible for their own learning".…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations